VARYASYON HESABININ OPTİMAL KONTROL SİSTEMLERİNE UYGULANMASI - TÜRKAN, HANİFİ (Fırat Üniveristesi, 2015)
Bu tezin amacı uygulamalı matematiğin ve mühendisliğin çeşitli dallarında kullanılan varyasyon hesabını ve optimal kontrolü tanıtmaktır. Bu nedenle öncelikle varyasyon hesabı ve optimal kontrol sistemleri ile ilgili temel bilgileri ortaya koymaktadır. Tezde optimal kontrol, optimizasyon, varyasyonlar hesabı ile ilgili bilgiler temel olarak kullanılmıştır. Optimal kontrol için varyasyonlar hesabının temel kavramları ve optimal kontrol sistemlerine uygulanması açıklanmıştır. Fonksiyonun optimumu hesaplanırken Lagrange çarpan metodundan yararlanılmıştır. Varyasyon hesabının optimal kontrol sistemlerine uygulanması yapılırken fonksiyonelin optimizasyonu, Lagrange denklem formu ve Hamilton denklem formu kullanılmıştır.

The aim of this thesis is to introduce optimal control and calculus of variation which are used in various branches of applied mathematics and engineering. In accordance with this, first it also manifests all the basic informations about calculus of variations and optimal control systems. In this thesis, information concerning optimal control, optimization and calculus of variations is explained in basic terms. Furthermore, for optimal control, basic informations about calculus of variations and applied to optimal control systems are explained. While calculating the optimum of the function, Langrange multiplier method was being utilized. While applying the Optimal Control Systems of the Calculus of Variations, optimization of the function, equation of Lagrange and eguation of Hamilton are used.
Applying the optimal control systems of the calculus of variations
Keywords: Matematik